2015
DOI: 10.5812/traumamon.23325
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stem Cell and Vein Conduit on Sciatic Nerve Repair in Rats

Abstract: Background:Peripheral nerve repair with sufficient functional recovery is an important issue in reconstructive surgery. Stem cells have attracted extensive research interest in recent years.Objectives:The purpose of this study was to compare the vein conduit technique, with and without the addition of mesenchymal stem cells in gap-less nerve injury repair in rats.Materials and Methods:In this study, 36 Wistar rats were randomly allocated to three groups: In the first group, nerve repair was performed with simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The conduit implantation investigations on the rat sciatic nerve use most often male rats weighing 200−250 g (Tao et al, ). Sprague Dawley (Hu et al, ; Zhuang et al, ) and Wistar rats (Abbasipour‐Dalivand, Mohammadi, & Mohammadi, ; Foroutan et al, ) are the most commonly used species, because articles analysis revealed that these strains are most commonly used in regeneration studies. The animals are kept in proper ventilation conditions at a suitable temperature (about 24 °C) and sufficient humidity (about 40−60%).…”
Section: The Necessary Work Before During and After The Conduit Impmentioning
confidence: 99%
“…The conduit implantation investigations on the rat sciatic nerve use most often male rats weighing 200−250 g (Tao et al, ). Sprague Dawley (Hu et al, ; Zhuang et al, ) and Wistar rats (Abbasipour‐Dalivand, Mohammadi, & Mohammadi, ; Foroutan et al, ) are the most commonly used species, because articles analysis revealed that these strains are most commonly used in regeneration studies. The animals are kept in proper ventilation conditions at a suitable temperature (about 24 °C) and sufficient humidity (about 40−60%).…”
Section: The Necessary Work Before During and After The Conduit Impmentioning
confidence: 99%
“…When the injured nerve underwent a high tensile stress by simple microsurgical repair, the best technique for reconstruction is nerve graft or nerve transfer [14][15][16][17]. Although up to now, many techniques including conduits, veins, and allografts have been used to cover finger's nerve defects, the best is to do autologous nerve graft [18][19][20]. Autografts are superior to the allografts because they are genetically identical with the recipient tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Direct treatment of damaged peripheral nerves with MSCs has also been demonstrated to be effective. Numerous encouraging animal studies have shown that stem or progenitor cell treatments can rescue some degree of neurological function after injury 54 , 55 , 56 ) ( Fig. 1 ).…”
Section: Possibilities In the Application Of Mscs To Regenerative Rehmentioning
confidence: 99%
“… 55 ) Seyed Foroutan K et al Trauma Mon, 2015. 56 ) Lasso JM, et al J Plast Reconstr Aesthet Surg, 2015. 58 ) MSCs in the rehabilitation of damaged cartilage Repair of damaged cartilage, cartilage healing, efficient recovery of function, without significant complications.…”
Section: Introductionmentioning
confidence: 99%